2018
DOI: 10.1155/2018/1952086
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Trough Levels and Quality of Life in Patients with Inflammatory Bowel Disease in Maintenance Therapy

Abstract: Objective Investigate the association between infliximab trough levels and quality of life in inflammatory bowel disease patients in maintenance therapy. Methods We carried out a transversal study with inflammatory bowel disease patients in infliximab maintenance therapy. Infliximab trough levels were determined using a quantitative rapid test. Disease activity indices (partial Mayo Score and Harvey-Bradshaw Index) and endoscopic scores (endoscopic Mayo Score or Simple Endoscopic Score in Crohn's disease) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
2
13
0
2
Order By: Relevance
“…The proportion of patients with supra-therapeutic levels was 17.46% according to Kampa et al in a study using ELISA kits that were shipped and analyzed in Leuven, Belgium, which also included UC patients (4). Similar supra-therapeutic levels were found by Parra et al (11.3%) in a study using the Quantum Blue rapid test (5). In another multicentric study, similar proportions were also found (8.16% with a different ELISA assay and 16.33% with the Quantum Blue rapid test) (6).…”
supporting
confidence: 87%
“…The proportion of patients with supra-therapeutic levels was 17.46% according to Kampa et al in a study using ELISA kits that were shipped and analyzed in Leuven, Belgium, which also included UC patients (4). Similar supra-therapeutic levels were found by Parra et al (11.3%) in a study using the Quantum Blue rapid test (5). In another multicentric study, similar proportions were also found (8.16% with a different ELISA assay and 16.33% with the Quantum Blue rapid test) (6).…”
supporting
confidence: 87%
“…In 2007, a European survey observed that 75.6% of IBD patients reported having symptoms that interfered with their ability to enjoy leisure activities, and almost 70% stated that their symptoms negatively affected work performance[11]. Patients with an active disease usually have poor QoL[2,12], but other studies[13,14] have observed that stress level, anxiety or depression, female gender, and fatigue can also contribute to poor QoL in IBD patients. Several studies[12,15,16] have also shown that IBD impacts work productivity.…”
Section: Introductionmentioning
confidence: 99%
“…We would like to thank Teixeira et al 1 for their comments on our article 2. They correctly noted that the majority of our patients presented infliximab (IFX) levels above the therapeutic concentration, differing from three other Brazilian studies published between 2017 and 2018 3-5. However, there are several significant conceptual and methodological differences between those studies and ours that need to be taken into consideration to understand the factors that led to such contrasting results.…”
mentioning
confidence: 68%
“…Teixeira et al 4 even suggested that more studies on patients with active disease would be necessary. Finally, Parra et al 5 evaluated the levels of IFX in a larger cohort of 55 patients with CD and 16 with UC. The novelty of this study was the use of a quality of life questionnaire and its correlation with the serum trough levels of IFX.…”
mentioning
confidence: 99%
See 1 more Smart Citation